Language Use and Communication Artifacts in GSM Adverts in Nigeria - Dada, Samuel Ayodele (Linguistik Online, 2010)
This is a sociolinguistic study of communication and language use in GSM adverts in Nigeria. The study was conducted to identify certain sociolinguistic strategies employed in GSM adverts in Nigeria. Our findings reveal that such strategies include: code choice, ethnography, semiotics and neologisms. The study has once again revealed that language choice especially in a multilingual community like Nigeria follows certain patterns and typology based on demographic, situational and attitudinal variants controlled by socio-cultural norms of communicative appropriateness.